Enacting leadership in formal and informal organisations: an empirical investigation on collective leadership practices - Souza, Renato José de (2019)
This dissertation analyses the production of collective leadership practices in two Brazilian multinational organisations (formal organisations) and in three community-based organisations located urban slums districts in Sao Paulo, Brazil (informal organisations). It examines the unfolding and development of leadership practices using a heuristic framework that encompasses six lenses of leadership: Person, Position, Process, Performance, Place and Purpose. This heuristic framework is used to investigate how collective leadership is created in these organisations. The dissertation is comprised of three articles. The first article is a theoretical essay that aims to discuss multiples lenses on studying leadership and their impact on how it is approached and theorized. The second article and third articles present the empirical findings from a systematic inquiry into individual, relational and collective leadership practices within community-based organisations and private sector organisations, respectively. Drawing on interview and observational data, I examine the factors (e.g., Position, Process, Performance, and Purpose) that either facilitate or hinder the emergence and impact of collective leadership. This dissertation advances in refining both theoretically and methodologically the collective-based approaches to leadership by providing a model for empirically examining these processes. It also lays out a framework for empirical inquiry in collective leadership across sectors. This multiple lens framework helps to foreground the ‘initiators’ of a collective effort and the ‘maintainers’ of collective practices, while it emphasises the multiple dimensions of collective leadership practices that inform how leadership development is articulated and practiced.